PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA RESTORAN PENDOPO - Niken Setiawati; Taufik Awaludin; Sam Cay; Amirudin (Journal of Research and Publication Innovation, 2025)
This research aims to determine the partial effect of work motivation on employee performance at Pendopo Restaurant, the partial effect of work discipline on employee performance at Pendopo Restaurant, and the simultaneous effect of work motivation and work discipline on employee performance at Pendopo Restaurant. This is a quantitative study, with a population of 50 respondents and a sample size of 50 respondents, using a saturated sampling technique. The method applied is quantitative. Data analysis includes validity testing, reliability testing, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The research results indicate that work motivation has a positive effect on employee performance. Work discipline also has a positive effect on employee performance. Additionally, both work motivation and work discipline have a positive effect on employee performance.